MODEL PENGEMBANGAN KINERJA ORGANISASI MELALUI KUALITAS JEJARING, KUALITAS KEPERCAYAAN DAN INOVASI - Tatiek Nurhajati (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
This research examines empirically and analyzes the influences of social capital in forms ofnetwork quality and trust, innovations of organizational performance. The populations in thisresearch were the medium furniture businesses in Central Java. This research took samplesas many as 127 respondents. The respondents were the managers/medium wooden furniturebusiness owners with the manpower ranging from 20 to 100 people. Data collection techniqueused questionnaires, and focus group discussion with the managers/ business owners. Theused technique of analysis was the Structural Equation Modeling. The examination on theinfluence of the moderation of environmental adaptability properties used the Multi-GroupedSequential Equation Modeling. The theoretical finding in this research is that, it is able to explain(1) uncertainty of the roles of social capital, network, and trust in improving organizationalperformance, (3) uncertainty of the role of innovation in mediating the social capital orientationon the organizational performance, (4) uncertainty of the role of environment moderating thecausal relationships among social capital, innovation, and organizational performance, and(6) it is able to add the literature concerning social capital orientation, especially the mattersconcerning wooden furniture medium business, which are still relatively limited.Keywords : Organizational Performance, Social Capital Orientation, Organizational Learning, Innovation